Investigation into Property and Bioactivity Polymeric Bone Cement - Abdullah, Yusof; Hayati Alias, Nor; Ee Abdullah, Nurhaslinda (Malaysian Journal of Science, 2002)
Polymeric bone cement is a bone repair material, which is able to give immediate augmentation of bone defects and accelerates normal bone healing through appropriate biodegradition rate. The simof the present study was to develop polymeric bone cement and to investigate the bioactivity of the bone cement produced was to develop polymeric bone cement and to investigate the bioactivity using Scanning Electron Microscope (SEM) and X-ray Diffraction technique (XRD). The bioactivity of the bone cement produced was tested under simulated body fluid (SBF) solution. In the present study, polymeric bone cement was developed frompoly (vinyl pyrrolidone) (PVP), unsaturated polyester poly (propylene fumigate), benzyl peroxide (BP) and hydroxyapatite (HA) by hand mixing. Benzyl peroxide initiated the cementing process while PVP accelerates to achieve cross linked between polyester chains. SEM observation of the cement after soaking in SBF showed the formation of new plate like apatite crystals in structure. Therefore, the developed bone cement has a potential as a repair material especially for cancellous bone.